Formulasi Kurikulum Pendidikan Islam: Prinsip, Nilai, dan Implementasi pada Lembaga Pendidikan - Prayitno, Abdul Afwu Godly; Arif, Mahmud (PAI Fakultas Tarbiyah & Ilmu Keguruan UIN SUNA Lhokseumawe, 2025)
Islamic education in Indonesia has developed through diverse institutional models, ranging from pesantren and madrasah to integrated Islamic schools. Each model presents a distinct approach to incorporating Qur’anic values into the curriculum. This article aims to analyse the foundations of ayat tarbawi (educational verses), the principles and values of Islamic education, and the implementation of curricula across different school models, with a particular emphasis on their relevance to contemporary educational needs. The study employs a qualitative approach based on a critical literature review, combining thematic exegesis of educational verses with conceptual analysis and institutional practices. The findings reveal that ayat tarbawi provide normative foundations such as tawḥīd (oneness of God), justice, compassion, lifelong learning, and freedom of thought. These principles are not merely theoretical but can be internalized through integrated curricula, moral habituation, and the adaptation of educational technology. At the implementation level, pesantren emphasize spiritual formation and scholarly tradition, madrasah promote the integration of religious and general sciences, while integrated Islamic schools adopt a modern model that combines the national curriculum with strengthened Islamic values. The synthesis underscores that Islamic education must bridge Qur’anic foundations with 21st-century demands, including digital literacy, critical thinking, and moral reinforcement. Hence, Islamic education is expected not only to preserve its spiritual identity but also to produce competitive, ethical, and globally relevant generations.